Manajemen stres dalam mencegah kecelakaan kerja dan meningkatkan kesejahteraan karyawan - Kusumawardana, Hendrawan; Amardhan, Shidqi Muhammad Zaini; Margana, Riki Ridwan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
In today’s industry, employee well-being has become a major concern for organizations as well as analysts in many fields. One of the important perspectives on employee well-being is Occupational Safety and Health (OHS), which plays a major role in maintaining productivity and sustainability of the work environment. Work stress, as a complex phenomenon, can have significant impacts on physical and mental health, leading to work accidents, decreased performance, and mental health disorders. This study uses a narrative synthesis approach to analyze relevant articles from databases such as PubMed, Scopus, and Google Scholar. The findings of this study highlight the importance of stress management in reducing the risk of work accidents, improving mental health, and employee well-being. The implications of this study emphasize the need for organizations to implement effective stress management strategies, with a focus on promoting mental health and social support. By adopting a comprehensive approach to occupational safety and health, organizations can create a safer and healthier work environment with improved employee well-being and organizational productivity.